ChemInform Abstract: An Overview of N‐Heterocyclic Carbenes. Issue 40 (30th September 2014) - Hopkinson, Matthew N.; Richter, Christian; Schedler, Michael; Glorius, Frank
Abstract Review: general properties and use; 100 refs.